VO2+ and Cu2+ Interactions with Ceftriaxone and Ceftizoxime. HPLC Kinetic Studies - Doadrio Antonio L.; Mayorga Antonio; Orenga Regina (Journal of the Brazilian Chemical Society, 2002)
Studies of the mechanism, kinetics and thermodynamic constants of VO2+ and Cu2+ Ceftriaxone and Ceftizoxime interactions at the pH range between pH 2 and 5 and at the temperatures of 30 º, 40 º, 50 º and 60 ºC, using reversed phase HPLC and ion exchange HPLC, are reported. The effects of pH, temperature and ion concentration on the hydrolysis reaction have been evaluated. HPLC studies provided satisfactory evidence of the reaction mechanism. Mechanisms for Cu2+ and VO2+ induced reactions involve a complex of 1:1 stoichiometry.